The regulation of autophagy differentially affects Trypanosoma cruzi metacyclogenesis. - María Cristina Vanrell; Antonella Denisse Losinno; Juan Agustín Cueto; Darío Balcazar; Laura Virginia Fraccaroli; Carolina Carrillo; Patricia Silvia Romano (Public Library of Science (PLoS), 2017)
Autophagy is a cellular process required for the removal of aged organelles and cytosolic components through lysosomal degradation. All types of eukaryotic cells from yeasts to mammalian cells have the machinery to activate autophagy as a result of many physiological and pathological situations. The most frequent stimulus of autophagy is starvation and the result, in this case, is the fast generation of utilizable food (e.g. amino acids and basic nutrients) to maintain the vital biological processes. In some organisms, starvation also triggers other associated processes such as differentiation. The protozoan parasite Trypanosoma cruzi undergoes a series of differentiation processes throughout its complex life cycle. Although not all autophagic genes have been identified in the T. cruzi genome, previous works have demonstrated the presence of essential autophagic-related proteins. Under starvation conditions, TcAtg8, which is the parasite homolog of Atg8/LC3 in other organisms, is located in autophagosome-like vesicles. In this work, we have characterized the autophagic pathway during T. cruzi differentiation from the epimastigote to metacyclic trypomastigote form, a process called metacyclogenesis. We demonstrated that autophagy is stimulated during metacyclogenesis and that the induction of autophagy promotes this process. Moreover, with exception of bafilomycin, other classical autophagy modulators have similar effects on T. cruzi autophagy. We also showed that spermidine and related polyamines can positively regulate parasite autophagy and differentiation. We concluded that both polyamine metabolism and autophagy are key processes during T. cruzi metacyclogenesis that could be exploited as drug targets to avoid the parasite cycle progression.